THE RELATIONS OF THE IMAGE AND FACT OF THE SERVICE QUALITY OF BUSWAY WITH USER LOYALTY - Dhany Utami Ningtyas; Tri Basuki Joewono (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2009)
The provision of bus rapid transit (busway) in Jakarta aims to provide a high service quality of publictransportation, to reduce congestion, and to improve the transportation system. In fact, the success of publictransportation depends on the acceptance and loyalty of the user. The image and experience of the userregarding the service quality also has a significant influence. Thus, the aim of this study is to explore therelations among constructs, i.e. user loyalty, image, and experience regarding the service quality of BRT.Responses from the user in the first corridor of BRT system was analyzed using structural equationmodeling. The results show that high image owned by the users regarding the service does not necessarilymean a high loyalty shown by the users. Analyses confirm the support of perceived service quality on theloyalty of the user in the future.Keywords: loyalty, image, fact, quality of service, busway